An electro-optical element in which potassium tantalate niobate crystal forms ohmic contact with an electrode and a preparation method thereof
Through ion doping and ultraviolet laser radiation technology, the annealing temperature in which the ohmic contact between the tantalum potassium niobate crystal and the electrode is reduced, the damage problem of high-temperature annealing on the crystal is solved, and high-quality electro-optical component preparation is achieved.
Patent Information
- Application Number
- CN202211521235.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-30
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2042-11-30
AI Technical Summary
In the existing methods of achieving ohmic contact between the tantalum potassium niobate crystal and the electrode, high annealing temperature leads to internal damage and poor usability of the crystal.
Ion-doped grown potassium tantalum niobate crystals are used and rapidly annealed under magnetron sputtering under ultraviolet laser irradiation to reduce the annealing temperature and reduce the damage to the crystal.
The annealing temperature required to achieve ohmic contact is effectively reduced, and the damage to the crystal by high-temperature annealing is reduced. The electro-optical elements produced have good optical quality and stable electrical properties.
Smart Images

Figure CN115786863B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of preparing electrodes of optoelectronic functional crystal devices, and in particular to an electro-optical element in which a potassium tantalate niobate crystal forms ohmic contact with an electrode, and a preparation method thereof. Background Art
[0002] Potassium tantalate niobate crystal (KTa 1-x Nb x O3, referred to as KTN) is an electro-optical crystal material with excellent performance. It has the largest known secondary electro-optic coefficient, and its electro-optical performance is 70 times that of the widely used lithium niobate crystal. Electro-optical devices designed based on KTN crystals have the advantages of low driving voltage, fast response speed and small device size, and can be widely used in medical imaging, laser processing and radar scanning.
[0003] At present, the basic components designed based on the electro-optic effect of KTN crystals mainly include electro-optic modulators and electro-optic deflectors. Electro-optic modulation usually requires the electrode to form a Schottky contact with the crystal, while electro-optic deflection requires the formation of an ohmic contact, that is, to ensure that the electrons in the metal electrode cross the surface potential barrier under the action of an applied voltage and enter the crystal to form a space charge, thereby forming an unevenly distributed empty charge field inside the crystal, and then forming a gradient refractive index distribution under the action of the secondary electro-optic effect to achieve beam deflection.
[0004] According to literature reports, KTN crystals can be regarded as N-type semiconductors, with oxygen vacancies in the crystal acting as donors to provide free electrons. If the influence of the surface state is not considered, the condition for the metal to form an ohmic contact with the N-type semiconductor is that the work function of the metal is smaller than the work function of the semiconductor. Based on this, when KTN crystals are used to achieve electro-optical deflection, most literature chooses to evaporate or sputter Ti metal on the surface of the KTN crystal as an electrode (Nakamura K, Miyazu J, Sasaki Y, et al. Space-charge-controlled electro-optic effect: Optical beam deflection by electro-optic effect and space-charge-controlled electrical conduction [J]. Journal of Applied Physics, 2008, 104 (1): 013105.), and believes that Au, Pt, etc. cannot form an ohmic contact on the surface of the KTN crystal. However, in the actual preparation process, a layer of Ti metal film is evaporated or sputtered on the surface of the KTN crystal as an electrode. In order to achieve ohmic contact, the coated crystal needs to be annealed. However, due to the high annealing temperature, the interior of the crystal is damaged. The optical quality of the annealed crystal is poor and cannot be used. In fact, the contact type between metal and semiconductor is also affected by many factors such as the doping concentration and interface state of the semiconductor. Therefore, whether the KTN crystal can form an ohmic contact with the surface metal electrode is not only related to the selection of metal materials, but also has a very close relationship with the preparation process. At present, there is no stable and reliable preparation process for ohmic contact between KTN crystal and electrode in the industry. Summary of the invention
[0005] In view of the technical problems in the existing method of realizing ohmic contact between potassium tantalate niobate crystal and electrode, such as high annealing temperature causing internal damage of the crystal and poor usability, the present invention provides an electro-optical element in which potassium tantalate niobate crystal forms ohmic contact with an electrode and a preparation method thereof.
[0006] In a first aspect, the present invention provides a method for preparing an electro-optical element in which a potassium tantalate niobate crystal forms an ohmic contact with an electrode, comprising the following steps:
[0007] (1) Using ion-doped grown potassium tantalate niobate crystals and performing optical-grade polishing on them;
[0008] (2) using magnetron sputtering to plate a metal film electrode on the surface of potassium tantalate niobate crystal;
[0009] (3) Rapidly annealing the coated crystal under ultraviolet laser irradiation.
[0010] The use of ion-doped potassium tantalate niobate crystals can not only effectively enhance the electro-optical efficiency of the crystal, but also reduce the width of the barrier between the metal and the crystal, making it easier for electrons or holes to tunnel, reducing the annealing temperature required to achieve ohmic contact. At the same time, adding laser irradiation during the annealing process can further reduce the required annealing temperature and reduce the damage to the interior of the crystal caused by high-temperature annealing. After annealing, the surface of the metal film electrode is flat and the edges are smooth and neat.
[0011] Furthermore, the rapid annealing parameters are: nitrogen as the protective gas, the annealing temperature is 350-600° C., the heating time is 1-3 min, and the annealing time is 5-10 min.
[0012] Furthermore, in step (1), the chemical formula of potassium tantalate niobate crystal is KTa 1-x Nb x O3, where x ranges from 0.2 to 0.5, and the doping ion is Cu 2+ or Fe 3+ or Cu 2+ , Fe 3+ Co-doping, in terms of molar percentage, has a doping concentration range of 0.1% to 1%.
[0013] Furthermore, the optical-grade polished surface roughness of the potassium tantalate niobate crystal is 0.1 to 10 nm.
[0014] Furthermore, before magnetron sputtering, the potassium tantalate niobate crystal is heated to 100-250° C., and bias sputtering is started to remove impurities on the surface of the potassium tantalate niobate crystal.
[0015] Furthermore, the material of the metal film electrode is one of Ti, Cr, Cu, Fe or Al, and the thickness is 30 to 100 nm.
[0016] Furthermore, a protective layer is plated on the outer side of the metal film electrode. The material of the protective layer is one of Au, Ag or Pt, and the thickness is 50 to 200 nm.
[0017] An inert metal is used as a protective layer to prevent the metal film electrode from being damaged, and the ohmic contact between the metal film electrode and the potassium tantalate niobate crystal is more stable.
[0018] Furthermore, the laser used for ultraviolet laser irradiation is one or more mixed continuous lasers with a wavelength range of 300 to 380 nm, and the laser power used is 500 to 1500 mW.
[0019] In a second aspect, the present invention provides an electro-optical element prepared by the above preparation method.
[0020] The beneficial effects of the present invention are:
[0021] The method for preparing an electro-optical element in which potassium tantalate niobate crystal forms ohmic contact with an electrode provided by the present invention adopts ion-doped potassium tantalate niobate crystal, which can effectively enhance the electro-optical efficiency of the crystal and reduce the potential barrier width between the metal and the crystal, making it easier for electrons or holes to tunnel, and reducing the annealing temperature required for achieving ohmic contact. At the same time, by adding laser irradiation during the annealing process, the annealing temperature for the potassium tantalate niobate crystal to form ohmic contact with the electrode is further reduced, and the damage to the interior of the crystal by high-temperature annealing is avoided. After annealing, the surface of the metal film electrode is flat, the edge is smooth and neat, and the prepared electro-optical element has good optical quality and stable electrical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0023] Figure 1 It is a schematic diagram of the preparation process of an electro-optical element in which a potassium tantalate niobate crystal forms an ohmic contact with an electrode in an embodiment of the present invention.
[0024] Figure 2 1 is a schematic diagram of the structure of an electro-optical element in which a potassium tantalate niobate crystal forms an ohmic contact with an electrode in an embodiment of the present invention;
[0025] Among them, 1. potassium tantalate niobate crystal, 21. first electrode, 22. second electrode.
[0026] Figure 3 This is the IV characteristic curve of the coated potassium tantalate niobate crystal before annealing in the embodiment of the present invention.
[0027] Figure 4 1 is the IV characteristic curve of the coated potassium tantalate niobate crystal after annealing in the embodiment of the present invention.
[0028] Figure 5 is the light spot diagram of the electro-optical element after annealing in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention;
[0029] Wherein a is the light spot diagram of the electro-optical element after annealing in Example 1, b is the light spot diagram of the electro-optical element after annealing in Comparative Example 1, and c is the light spot diagram of the electro-optical element after annealing in Comparative Example 2. DETAILED DESCRIPTION
[0030] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0031] Example 1
[0032] A method for preparing an electro-optical element in which a potassium tantalate niobate crystal forms an ohmic contact with an electrode, comprising the following steps:
[0033] (1) Potassium tantalate niobate crystal grown by the Czochralski method, chemical formula KTa 1-x Nb x In O3, x=0.37, the growth material is doped with CuO, and the doping concentration is 0.1% by mole percentage. It is processed into the required size and shape according to the requirements of electro-optical deflection applications, such as 3mm×2mm×4mm. The light-transmitting surface and electrode-plated surface of the crystal are ground and polished, and the surface roughness reaches 1nm.
[0034] (2) Before electrode plating, the potassium tantalate niobate crystal is ultrasonically cleaned and blown clean with nitrogen. A magnetron sputtering apparatus equipped with dual targets is used for coating. First, the crystal temperature is heated to 100°C, bias sputtering is turned on to remove impurities on the crystal surface, and then DC sputtering is used to sputter a layer of Ti metal film with a thickness of 50nm on the crystal surface, and then a layer of Au metal film with a thickness of 100nm is sputtered to form a double-layer metal film electrode. The equipment parameters during the sputtering process are set as follows: argon gas flow rate 10sccm, DC power supply power 350W, and chamber pressure 0.8Pa during sputtering. After sputtering, it is naturally cooled to room temperature. Flip the sample over and sputter the other side using the same process to obtain a coated potassium tantalate niobate crystal.
[0035] (3) Select a rapid annealing furnace, place the coated potassium tantalate niobate crystal, evacuate the vacuum and then introduce nitrogen, heat up for 1 minute, anneal at 400°C, and anneal for 8 minutes. During the annealing process, a 365nm ultraviolet laser is used for irradiation, with a laser power of 800mW. After naturally cooling to room temperature, the ohmic contact electrode of the potassium tantalate niobate crystal is fabricated to form an electro-optical element. The metal film electrode of the electro-optical element is flat, with smooth and neat edges, and a structure such as Figure 2 As shown, the electro-optical element includes a potassium tantalate niobate crystal 1 , a first electrode 21 and a second electrode 22 .
[0036] Example 2
[0037] A method for preparing an electro-optical element in which a potassium tantalate niobate crystal forms an ohmic contact with an electrode, comprising the following steps:
[0038] (1) Potassium tantalate niobate crystal grown by top seed solution method, chemical formula KTa 1-x Nb x In O3, x=0.2, and the growth material is doped with Fe2O3, with a doping concentration of 1% by mole. It is processed into the required size and shape, such as 4mm×4mm×1mm, according to the requirements of electro-optical deflection applications. The light-transmitting surface and electrode-plated surface of the crystal are ground and polished, and the surface roughness reaches 0.1nm.
[0039] (2) Before electrode plating, the potassium tantalate niobate crystal is ultrasonically cleaned and blown clean with nitrogen. A magnetron sputtering apparatus equipped with dual targets is used for coating. First, the crystal temperature is heated to 250°C, and bias sputtering is turned on to remove impurities on the crystal surface. Then, DC sputtering is used to sputter a 100nm thick Cu metal film on the crystal surface, and then a 20nm thick Pt metal film is sputtered to form a double-layer metal film electrode. The equipment parameters during the sputtering process are set as follows: argon flow rate of 20sccm, DC power supply power of 400W, and chamber pressure of 1Pa during sputtering. After sputtering, it is naturally cooled to room temperature. Flip the sample over and sputter the other side using the same process.
[0040] (3) A rapid annealing furnace is selected, and the coated potassium tantalate niobate crystal is placed in it. After vacuuming, nitrogen is introduced. The heating time is 1 minute, the annealing temperature is 350°C, and the annealing time is 10 minutes. The annealing process is irradiated with a 355nm ultraviolet laser with a laser power of 1500mW. After naturally cooling to room temperature, the ohmic contact electrode of the potassium tantalate niobate crystal is completed to form an electro-optical element.
[0041] Example 3
[0042] A method for preparing an electro-optical element in which a potassium tantalate niobate crystal forms an ohmic contact with an electrode, comprising the following steps:
[0043] (1) Potassium tantalate niobate crystal grown by top seed solution method, chemical formula KTa 1-x Nb x O3, x=0.5, the growth material is co-doped with Fe2O3 and CuO, in molar percentage, the Fe2O3 doping concentration is 0.2%, and the CuO doping concentration is 0.3%. It is processed into the required size and shape according to the requirements of electro-optical deflection applications, such as 2mm×2mm×5mm, and the light-transmitting surface and electrode-plated surface of the crystal are ground and polished, and the surface roughness reaches 0.5nm.
[0044] (2) Before electrode plating, the potassium tantalate niobate crystal is ultrasonically cleaned and blown clean with nitrogen. A magnetron sputtering device equipped with dual targets is used for coating. First, the crystal temperature is heated to 100°C, and bias sputtering is turned on to remove impurities on the crystal surface. Then, DC sputtering is used to sputter a 30nm thick Cr metal film on the crystal surface, and then a 150nm thick Ag metal film is sputtered to form a double-layer metal film electrode. The equipment parameters during the sputtering process are set as follows: argon flow rate 30sccm, DC power supply power 250W, and chamber pressure 2Pa during sputtering. After sputtering, it is naturally cooled to room temperature. Flip the sample over and sputter the other side using the same process.
[0045] (3) A rapid annealing furnace is selected, and the coated potassium tantalate niobate crystal is placed in it. After vacuuming, nitrogen is introduced. The heating time is 3 minutes, the annealing temperature is 600°C, and the annealing time is 5 minutes. During the annealing process, a 375nm ultraviolet laser is used for irradiation, and the laser power is 500mW. After naturally cooling to room temperature, the ohmic contact electrode of the potassium tantalate niobate crystal is completed to form an electro-optical element.
[0046] The IV characteristic curves of the coated potassium tantalate niobate crystals of Examples 1-3 before and after annealing measured using the C-TLM electrode structure are as follows: Figure 3 and Figure 4 As shown, it is proved that the potassium tantalate niobate crystal and the metal film electrode are in Schottky contact before annealing, and the potassium tantalate niobate crystal and the metal film electrode achieve ohmic contact after annealing.
[0047] Comparative Example 1
[0048] The difference from Example 1 is that the raw material for crystal growth is not doped with CuO, and other treatments are consistent with Example 1. During the annealing process, the annealing temperature needs to be increased to above 760° C. to achieve ohmic contact between the potassium tantalate niobate crystal and the metal film electrode.
[0049] Comparative Example 2
[0050] The difference from Example 1 is that the rapid annealing process does not use laser irradiation, and other treatments are consistent with Example 1. During the annealing process, the annealing temperature needs to be increased to above 820°C to achieve ohmic contact between the potassium tantalate niobate crystal and the metal film electrode.
[0051] Figure 5 a is the light spot diagram of the electro-optical element prepared in Example 1, showing no obvious distortion. Figure 5 b is the light spot diagram of the electro-optical element prepared in comparative example 1. The higher annealing temperature causes damage to the crystal, resulting in poor quality of the light spot of the crystal. Figure 5c is the light spot diagram of the electro-optical element prepared in comparative example 2, which also caused thermal damage to the crystal. It can be seen that the addition of ion doping and laser irradiation technology reduces the annealing temperature of the potassium tantalate niobate crystal and the electrode to form an ohmic contact, avoids the damage of the crystal by high-temperature thermal annealing, and successfully produces an electro-optical element with high optical quality potassium tantalate niobate crystal and electrode to form an ohmic contact.
[0052] Although the present invention has been described in detail with reference to the accompanying drawings and in combination with the preferred embodiments, the present invention is not limited thereto. Without departing from the spirit and essence of the present invention, a person of ordinary skill in the art may make various equivalent modifications or substitutions to the embodiments of the present invention, and these modifications or substitutions shall be within the scope of the present invention. Any person of ordinary skill in the art may easily think of changes or substitutions within the technical scope disclosed by the present invention, and these shall be within the scope of protection of the present invention.
Claims
1. A method for preparing an electro-optical element in which a potassium tantalate niobate crystal forms an ohmic contact with an electrode, characterized in that: The steps include: (1) Potassium tantalate niobate crystal grown by ion doping. The chemical formula of potassium tantalate niobate crystal is KTa 1-x Nb x O3, where x ranges from 0.2 to 0.5, and the doping ion is Cu 2+ or Fe 3+ Cu 2+ , Fe 3+ Co-doping, in mole percentage, with a doping concentration range of 0.1% to 1%, is performed with optical grade polishing; (2) using magnetron sputtering to plate a metal film electrode on the surface of potassium tantalate niobate crystal, wherein the material of the metal film electrode is one of Ti, Cr, Cu, Fe or Al; (3) The coated crystal was rapidly annealed under ultraviolet laser irradiation. The laser power used was 500~1500mW. The rapid annealing parameters were: nitrogen as the protective gas, annealing temperature of 350~600℃, heating time of 1~3min, and annealing time of 5~10min.
2. The preparation method according to claim 1, characterized in that The surface roughness of optical-grade polished potassium tantalate niobate crystal is 0.1~10nm.
3. The preparation method according to claim 1, characterized in that: Before magnetron sputtering, the potassium tantalate niobate crystal is heated to 100-250°C, and bias sputtering is turned on to remove impurities on the surface of the potassium tantalate niobate crystal.
4. The preparation method according to claim 1, characterized in that: The thickness of the metal film electrode is 30~100nm.
5. The preparation method according to claim 1, characterized in that: A protective layer is plated on the outside of the metal film electrode. The material of the protective layer is one of Au, Ag or Pt, and the thickness is 50~200nm.
6. The preparation method according to claim 1, characterized in that: The laser used for ultraviolet laser irradiation is one or more mixed continuous lasers with a wavelength range of 300~380nm.
7. An electro-optical element prepared by the preparation method according to any one of claims 1 to 6.
Citation Information
Patent Citations
Silicon carbide semiconductor device and method for manufacturing the same
US20190259615A1